Nonlinear piezoelectric properties of epitaxial BaTiO3 thin film. (4th July 2017) - Negulescu, B.; Daumont, C. J. M.; Sakai, J.; Ruyter, A.; Bavencoffe, M.; Alyabyeva, N.; Wolfman, J.
ABSTRACT: The piezoelectric properties of epitaxial BaTiO3 film were studied by double laser Doppler vibrometry. As expected for a ferroelectric material, the piezoelectric response of the structure is hysteretic. The d33 value is reduced from a maximum 42 pm/V to 25 pm/V when increasing the DC bias, indicating the large influence of extrinsic effects close to the coercive fields. Using a Rayleigh approach, the slight nonlinearity of the piezoelectric response as a function of the AC field was attributed to irreversible domain wall displacements. At high AC electric fields the strain saturates. The second harmonic response of the system was associated to the piezoelectric activity.